Automated auditory response detection: Further improvement of the statistical test strategy by using progressive test steps of iteration. (August 2015) - Cebulla, Mario; Stürzebecher, Ekkehard
Abstract: Objective: A common testing approach for automated ABR detection is to use a sequential test strategy. Repeated testing increases the error probability for a falsely detected response (Type I error rate). To compensate for this effect, the statistically critical test value must be increased with each test step. The aim of the study was to improve response detection by a reduction of the number of test steps using a progressively increasing test step of iteration, defined here as step width. Design: A progressively increasing test step width was tested with and without the table-related testing (adjusting the critical test value to each test step) proposed byStürzebecher & Cebulla (2013) . For this study the same data pool was used. Study sample: The investigation was performed on raw EEG data collected during routine clinical measurement of frequency-specific ASSR for hearing threshold assessment. Results: The reduction of the test step number combined with a progressive test step width led to a significantly improved response detection. In combination with table-related testing a slight but not significant improvement compared to table-related testing alone was revealed. Conclusions: The proposed test strategy can improve the performance of objective hearing threshold assessment and of newborn hearing screening.